2009
DOI: 10.1021/jm801395v
|View full text |Cite
|
Sign up to set email alerts
|

Specific Targeting of Highly Conserved Residues in the HIV-1 Reverse Transcriptase Primer Grip Region. 2. Stereoselective Interaction to Overcome the Effects of Drug Resistant Mutations

Abstract: Starting from the prototypic compound 4, we describe new, potent, and broad-spectrum pyrrolobenzo(pyrido)oxazepinones antivirals. A biochemical and enzymological investigation was performed for defining their mechanism of inhibition at either recombinant HIV-1 RT wild type and non-nucleoside reverse transcriptase inhibitors (NNRTIs)-resistant mutants. For the novel compounds (S)-(+)-5 and (S)-(-)-7, a clear-cut stereoselective mechanism of enzyme inhibition was found. Molecular modeling studies were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
6
0
2
Order By: Relevance
“…The observation that mutations in the NNRTI BP that increased EFV and ETR resistance were sensitive to the resistance-enhancing effect of RNase H cleavage activity is consistent with this hypothesis. The NNRTI BP mutations analyzed in our studies were previously shown to reduce the affinity of NVP and EFV to the RT and RT-T/P (8,31,47,53,61). Although there is no biochemical data available at this time, it is likely that NNRTI BP mutations that confer resistance to DLV and ETR also reduce the affinity of these drugs to the mutant RTs (10,16).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The observation that mutations in the NNRTI BP that increased EFV and ETR resistance were sensitive to the resistance-enhancing effect of RNase H cleavage activity is consistent with this hypothesis. The NNRTI BP mutations analyzed in our studies were previously shown to reduce the affinity of NVP and EFV to the RT and RT-T/P (8,31,47,53,61). Although there is no biochemical data available at this time, it is likely that NNRTI BP mutations that confer resistance to DLV and ETR also reduce the affinity of these drugs to the mutant RTs (10,16).…”
Section: Discussionmentioning
confidence: 84%
“…To test the hypothesis that the affinity of the NNRTI to the RT is a key component in determining whether reducing RNase H activity affects NNRTI resistance, we created NNRTI-resistant RT mutants with amino acid substitutions L100I, K103N, V106A, V179F, and Y181C in the NNRTI BP that alter the binding characteristics of the mutant RTs for the NNRTIs (8,31,47,53,61). The effects of most of these NNRTI resistance mutations, as well as other mutations, on NVP and EFV affinity to the RT are summarized in Table 2.…”
Section: Affinity Of Nnrtis To the Rt Is A Critical Parameter In Detementioning
confidence: 99%
“…Given that most NNRTIs against HIV-1 RT are not active against HIV-2 RT (37), it is unlikely that the already established anti-HIV-1 drugs will be active against the more distantly related HBV P protein. However, by the screening of compound libraries that maintain the principal HIV-1 NNRTI butterfly-like shape (13,35) and by advanced modeling, NNRTIs with activity against HBV should be identifiable. Because all current anti-HBV therapies beyond type I interferon rely exclusively on nucleos(t)ide analogs, such NNRTIs, with their different mechanism of action, would be a most desired alternative for, or complement to, the limited drug repertoire available against chronic hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…Together with HIV-1 RT homology-based modeling and the functionality of chimeric P proteins carrying box E, or even the sequence encompassing the catalytic YMDD motif in box C to box E, from HIV-1 RT, these data demonstrate a common catalytic core architecture of the RT domains of hepadnaviral P proteins and retroviral RTs, in particular the formation of a primer grip-like structure by the box E residues in P proteins. Because the primer grip in HIV-1 RT is the target for multiple approved and experimental NNRTIs (13,18), the presence of a primer grip equivalent in P proteins suggests that related compounds might be developed into a new class of HBV inhibitors.…”
Section: Figmentioning
confidence: 99%
“…Pyrrolo-1,5-benzoxazepines (PBOXs) and pyrrolonaphthoxazepines (PNOXs) are pharmaceutically relevant heterocycles. As a part of our research activity, a major focus was directed toward the development of novel PBOXs and PNOXs as potent antitumor agents, inhibitors of adenosine kinase and nonnucleoside inhibitors of human immunodeficiency virus reverse transcriptase (HIV-1 RT) [1][2][3][4][5][6][7][8][9][10][11][12]. In particular, our continuing efforts in the field of antitumor agents led to the development of PBOX-and PNOXbased compounds as potent proapoptotic agents [4].…”
mentioning
confidence: 99%